Novel swine models for influenza A virus infection - Kwon, Taeyong (My University, 2025)
Influenza A virus (IAV) is an enveloped, negative-sense RNA virus, with an eight-segmented genome. IAV has a wide range of host tropisms from birds to mammals, including humans, and can cross inter-species barriers to broaden the host range. Pigs are an important reservoir for IAV ecology and have been used as an animal model for IAV research. Therefore, in this collection of work, several different swine models have been developed to better understand IAV infection dynamics and its interaction with host immune responses. Here, we established the swine pathogenesis model to study the pathogenicity and transmissibility of the newly emerged highly pathogenic avian influenza (HPAI) H5N1 viruses. The results supported that pigs are susceptible to experimental infections with HPAI viruses but do not transmit to sentinel pigs. Next, we established gene-edited pigs that are resilient to IAV infection. Experimental infection led to a significant reduction of virus shedding in the upper respiratory tract, and lower virus titers and pathological lesions in the lower respiratory tract of TMPRSS2 KO pigs as compared to wild-type pigs, which, in turn, disrupted IAV transmission in TMPRRS2 KO pigs. Lastly, we established a gene-edited pig model to elucidate innate T cell immunity. Using CD1d-deficient pigs, it was shown that NKT cells play critical roles in modulating immune responses and contribute to vaccine-associated enhanced respiratory diseases. In conclusion, our results provide novel insights and better understanding of IAV pathogenesis in pigs.
Keywords: Swine; Pig; Influenza A virus